ASSOCIATION OF METABOLIC SYNDROME AND SUBCLINICAL HYPOTHYROIDISM PATIENTS ATTENDING CHITWAN MEDICAL COLLEGE - Kafle , Deepak; Mandal , Fuleshwar; Timalsina , Santosh; Khadka , Bikram (Journal of Chitwan Medical College, 2022)
Background: Metabolic syndrome is characterized by a cluster of cardiovascular risk factors such as abdominal obesity, dyslipidemia, hyperglycemia, and hypertension. Subclinical hypothyroidism is defined as an increase in serum levels of thyroid stimulating hormone (TSH) above the normal range, without alteration of total T4 concentrations has been associated with various metabolic alterations. The study aimed to investigate association between metabolic syndrome and subclinical hypothyroidism patients attending Chitwan Medical College. Methods: This cross-sectional study consisted of 250 randomly selected individuals visiting OPD in the Department of Medicine of Chitwan Medical College 10ml of blood sample was drawn from antecubital vein following overnight fasting. Fasting blood sugar, lipid profile and thyroid profile etc. were analyzed via chemiluminescence Analyzer at Hospital Laboratory and was statistically analyzed. Results: The association of BMI with T4 and TSH was found to be positively correlated and was significant at P<0.05 but the association of systolic blood pressure (SBP) with T3 was not significant but there was negatively significant correlation of SBP with T4 and TSH. The correlation of diastolic blood pressure (DBP), TG, HDL, fasting blood sugar were not significant with T3, T4 and TSH at p<0.05. BMI was positively correlated with T4 and TSH (r = 0.12, P<0.05 and r=0.81, P<0.001) whereas SBP was negatively correlated with T4 and TSH (r = -0.12, P<0.05 and r=-0.16, P<0.001 respectively). Conclusions: From our study it was concluded that the association of BMI with T4 and TSH was found to be positively correlated in subclinical hypothyroidism subjects.